A tutela inibitória e a efetividade do processo - Eduardo Calais Pereira (2014)
This dissertation is mainly aimed to investigate and understand the phenomenon of prohibitory injunction and on what extent, the institute may influence the effectiveness of the lawsuit. The compensatory injunction, historically placed as the principal means of performance of the jurisdiction, proved to be insufficient for the protection of some rights, notably the non-material ones. In this context, the prohibitory injunction is the only appropriate means to provide protection to those rights, which once violated, may not be compensated by any monetary amount. From a critical analysis, to reflect the most questionable points of this subject, proceeded to a historical, doctrinal, jurisprudential investigation, in order to delimit the most controversial issues that are relevant to the effectiveness of the lawsuit. Analyzing by comparative law other institutes, such as référé, in France, and self-satisfactory measures, in Argentina, sought to demonstrate the different ways that can serve as a means for the construction of the prohibitory injunction. The study also took place on constitutional scope, investigating possible conflicts between the right to information (particularly journalistic) and the right to privacy, intimacy, honor and image on prohibitory injunction scope, taking into consideration the understanding set by STF on the judgment of ADPF 130. At the end, it was analyzed some theories of effectiveness of the lawsuit, in order to demonstrate the contribution of prohibitory injunction for that. It is intended thus, on the development of this study, to present, based on the considered hypothesis, how the prohibitory injunction plays the essential role to increase the effectiveness of the lawsuit.